Instruments of stabilization policy and their application in South Africa between 1960 and 1972 - Colburn, Alan Richard Harold (School of Economics, 2024)
The objectives of stabilization policy are widely accepted: firstly to maintain a high rate of utilization of resources, secondly to preserve a reasonably stable price level, or, more realistically nowadays, to maintain a low rate of inflation, and finally to accomplish the first two goals with the maintenance of a viable balance of payments position. The indicators of success of stabilization policy are then, obviously, the unemployment rate and the level of unutilised capacity, the consumer and wholesale indices, and the level of gold and foreign exchange reserves. A topic of much concern is the extent to which the fluctuations in these three series can be attributed to measures implemented by the authorities responsible for stabilization policy. The subject matter of this dissertation stems from this concern. This dissertation, however, does not attempt to derive some overall quantitative impact of stabilization policies, but rather sets out to highlight problems with the policy instruments in particular with respect to their lag structures, uncertainty as to their impacts and the duration of the impact and their side-effects. From this and recent theoretical developments, and having noted the manner in which stabilization policies were pursued in South Africa, proposals regarding the improved conduct of stabilization policies are tentatively put forward in the concluding chapter. Control of the money supply has fairly recently been re-elevated to a position of importance in the view of many economists f or its potential role as an anti-inflationary me8sure. As will be indicated, the South African authorities have tended to focus attention on the level of interest rates as an indicator of monetary policy rather than on the money supply. To explain the academic backing to this priority a discussion of the recent 'money matters' debate is pursued in Chapter 11.